Hydrochemical Facies of Groundwater in Thi Qar Governorate (South Iraq) - Al-Obaidi, Mutadhid (Iraqi Journal of Science, 2018)
This research discusses the quality of hydrochemical facies of groundwater for selected wells in Thi Qar governorate south Iraq. Physical properties (pH, TDS, EC, TH) were conducted for all samples . The results indicated that this groundwater is neutral and light alkaline, slightly-brackish, excessively mineralized and hard to very hard water. Analyses of cations and anions are carried out to determine two hydrochemical facies, they are " earth alkaline water with increased portions of alkalis with prevailing sulfate and chloride" and " Alkaline water with prevailing sulfate and chloride" belong to (Ca2+ - Mg2+ - Cl- - SO4 2- ) and (Na+- K+ - Cl- - SO4 2-). Concerning evaluation of groundwater suitability for different purposes, It turned out that this groundwater is unsuitable for human drinking and industrial purposes, satisfactory for livestock . And what about suitability for irrigation purposes, It ranged between unsuitable to doubtful according to ( Na%) and RSC , but it was excellent to good limits according to SAR.